Synthesis and Characterization of Imidazo[1,2-a]pyridines and Zolimidine - Kushwaha, Narva Deshwar; Mondal, Somnath; Sharma, Renu; Kumar, Naresh (Asian Journal of Chemistry, 2017)
A convenient and efficient synthesis, without any organic solvent or catalyst is described for the preparation of imidazo[1,2-a]pyridine derivatives. The reaction has been done between 2-aminopyridines and a-bromoacetone derivatives in good to excellent yields in water. In several cases the isolation does not require any chromatography for purification. The reaction thus developed has been applied for quick synthesis of zolimidine with 91 % yield.